2008
DOI: 10.1007/s11920-008-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder and suicide: Research synthesis and clinical translation

Abstract: Attempted suicide and suicide are prevalent in individuals with bipolar disorder (BD). Extant evidence indicates that history of suicide attempts, percentage of time spent in a depressed state, and hostility are factors associated with suicide attempts and completed suicide. Childhood adversity (eg, sexual and physical abuse) is emerging as a risk factor for suicide attempts in adults with BD. The pertinacity of medical comorbidity (eg, obesity, metabolic syndrome) in the bipolar population is further undersco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 50 publications
0
47
0
6
Order By: Relevance
“…Consistently, the G allele was associated with SB, psychomotor agitation, thoughts of death, irritability and higher depression severity at the severest depressive episode. It is interesting to note that these specific clinical factors associated with the GG genotype and G allele in our sample have already been associated with SB in the BD population in clinical studies [50][51][52] . These data suggested that the SIRT1 genotype may be associated with different clinical phenotypes of bipolar depression and, at least indirectly, with SB.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Consistently, the G allele was associated with SB, psychomotor agitation, thoughts of death, irritability and higher depression severity at the severest depressive episode. It is interesting to note that these specific clinical factors associated with the GG genotype and G allele in our sample have already been associated with SB in the BD population in clinical studies [50][51][52] . These data suggested that the SIRT1 genotype may be associated with different clinical phenotypes of bipolar depression and, at least indirectly, with SB.…”
Section: Discussionmentioning
confidence: 64%
“…These data suggested that the SIRT1 genotype may be associated with different clinical phenotypes of bipolar depression and, at least indirectly, with SB. In other words, rs10997870 may be associated with a clinical en- dophenotype of BD depression, characterized by psychomotor agitation, thoughts of death, irritability and higher depression severity, which in turn is associated with SB in the BD population [50][51][52] . Obviously, data are still lacking to better disentangle this issue, and further studies are needed to better clarify the associations found till now.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] For example, suicide attempts and bipolar disorder severity have been linked to childhood sexual (CSA) and physical abuse (CPA). [42][43][44] Primate studies suggest that early life adversity alters stress sensitivity-a feature of both SBs and MDs-compromising serotonergic neurotransmission. 45,46 Stress is, for example, associated with SLC6A4 mRNA level 47 and harsh parenting to HTR2A receptor density.…”
Section: Introductionmentioning
confidence: 99%
“…En el segundo caso, el EDM representa uno de los llamados "polos" del Trastorno Bipolar (TB), cuya prevalencia estimada en Chile es de 2,2± 0,5% (promedio y error estándar) 6 . En otras palabras, en nuestro país potencialmente alrededor de 300 mil personas sufren de TB, condición asociada con una tasa de suicidio de 10 al 15% 7 , abuso de alcohol y drogas 8 , y un impacto muy negativo en el trabajo y la vida familiar y social 9 . Como todo trastorno psiquiátrico, el TB debe ser diagnosticado usando criterios estandarizados y la queja del paciente de tener "cambios bruscos de ánimo" debe ser sólo el comienzo de una evaluación clínica que debe evitar la presión derivada de "modas" diagnósticas.…”
Section: Glosario De Términos Usados En El Textounclassified